LAND-USE CHANGES AND THE INCREASE IN THE NUMBER ROAD-STREAM CROSSINGS IN A RURAL BASIN SOUTH OF BRAZIL - França Junior, Pedro; Thomaz, Edivaldo Lopes (Revista Brasileira de Geomorfologia, 2018)
Changes in land use interfere with river basin connectivity, affecting the flow dynamics, sediment yield, and density of river connections with roads. In this research we studied the variation of land use from 1980-2002-2016 using vector mappings in the classes: temporary crops, primary and secondary forests; pasture, forestry, buildings, ponds, and the development of crossings between drainage roads (road-stream crossings) in the Guabiroba River basin. Variations in the use and percentages over the 36 years studied were observed. There was a reduction in primary forest and pasture areas and an increase in planted forests and temporary crops. Regarding the crossings, there was an increase in the topographic dimensions and in sectors with sharp slopes and first-order channels. Over the years, the uses in the basin were alternated according to the productive structures, showing needs according to the creation, modification, and suppression of roads. In temporary crops, the period from planting to harvesting is up to 6 months, and slash-and-burn agriculture rage from 3 to 5 years between each planting, and forestry depending on the demands it can range from 4 to 20 years. These variations in time and space, interfere with the productive flows and consequently with the road-stream crossings.